Parental experience of change following VIPP-SD in families with preschool children with externalizing behavior: A qualitative interview study. - Nina M Lassen; Tine Steenhoff; Bryan Cleal; Amanda Frees; Mette S Væver (PLoS ONE)
Background Insensitive parenting and ineffective disciplinary strategies are known risk factors for child externalizing behavior. The Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) has documented effect in promoting sensitive parenting, but little is known on how VIPP-SD is experienced by parents. This study explores how parents of preschool children with externalizing behaviors experience change following VIPP-SD delivered by trained childcare providers. Methods Individual qualitative semi-structured interviews were conducted with 9 mothers and 2 fathers to explore the parents' experiences of change following the intervention. Data were analyzed using Braun and Clarke's reflexive thematic analysis. Results Four themes were generated: 1) "All of her behavior is actually just a result of how she feels, right?"-Enhanced parental understanding, 2) Meeting the child's needs in comfort and in play, 3) Learning to prevent and manage conflicts is essential-diverse experiences of gains and progress, 4) "I'm actually not a bad parent"-new positive perspectives. Conclusion Parents experienced an enhanced capacity to understand their child and positive development in their parenting behavior, skills and confidence as well as improvements in the parent-child relationship after receiving VIPP-SD. Findings also suggest potential areas for adaptation of VIPP-SD when intervening in families with a child exhibiting externalizing behaviors, as parental experiences of gains related to conflict management varied. Further research on this matter is recommended.